Market Orientation, Export Marketing Performance, and the Mediating Role of Product Adaptation Strategy in Indonesian Coffee Smes - Rohwiyati; Tulus Haryono; Lilik Wahyudi; Ahmad Ikhwan Setiawan; Kusumaningdiah Retno Setiorini (Kurdish Studies, 2023)
The development of market orientation theory as a key element in improving company export marketing performance, it turns out that studies on the export marketing performance of small and medium enterprises (SMEs) in Indonesia are still very lacking. Two dimensions of market orientation, namely customer and competitor orientations, are analyzed as constructs to prove their resilience to increasing the export performance of coffee SMEs in Indonesia. Arguments from a theoretical point of view are used to separate customer and competitor orientations. The aim of this research is to empirically examine customer and competitor orientations on SMEs export marketing performance separately. Apart from that, this research also examines the role of product adaptation strategies in encouraging the export marketing performance of SMEs in Indonesia.The sample for this research was 97 SME coffee farmers in Central Java who met the requirements to be used in the research. Data analysis used Partial Least-Square Structural Equation Modeling (PLS SEM). The sample criteria for this research were specific to coffee SMEs that exporting. Therefore, it will strengthen the generalization of previous research results. Samples were obtained from the Central Java coffee SME database published by the Indonesian Central Java Province Agriculture and Plantation Service, using a non-random sampling technique. The findings of the research indicate that product adaptation strategy is proven to mediate the relationship among customer and competitor orientation and export marketing performance. Customer orientation was found to have no significant relationship with export marketing performance, while competitor orientation and product adaptation strategy were found to positively influence export marketing performance.The role of product adaptation strategy as a mediator of the relationship between customer orientation and competitor orientation on export marketing performance opens the way for further research in other developing countries. By examining the concepts of customer and competitor orientation separately but in relationship, we validate support for this argument from both methodological and theoretical viewpoints.